A novel dendritic cell-targeted lentiviral vector, encoding Ag85A-ESAT6 fusion gene of Mycobacterium tuberculosis, could elicit potent cell-mediated immune responses in mice. (July 2016) - Shakouri, Mehdi; Moazzeni, Seyed Mohammad; Ghanei, Mostafa; Arashkia, Arash; Etemadzadeh, Mohammad Hossein; Azadmanesh, Kayhan
Highlights: We developed a novel DC-directed lentivector, LV-GFP/SVGmu that could specifically transduce DC-SIGN-expressing cells with a high efficiency. The DC- directed lentivector, LV-AEG/SVGmu, was also able to successfully transduce and express the fusion antigen Ag85A-E6-GFP in DC-SIGN-expressing cells. A single footpad injection of LV-AEG/SVGmu could elicit significant elevated cellular and humoral immune responses in mice. Hence, it can be considered as a novel candidate for vaccine research and immunotherapy in future. Abstract: Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis (Mtb), leading to high mortality worldwide. It is well-established that cellular immunity plays a critical role to control Mtb infection. Dendritic Cells (DCs) are potent antigen presenting cells, which play an important role to prime cell-mediated immune responses. In vivo targeting of DCs has been shown to induce both strong cellular immunity and protection against tumor challenges. The aim of the present study was not only to assess the immunizing potential of a novel DC-targeted recombinant lentivirus expressing fusion antigen Ag85A-ESAT6 of Mtb, but also to compare it with a recombinant lentivirus with broad cellular tropism expressing the same antigen in mice. The findings demonstrated that our novel recombinant DC-targeted lentivector was able to successfully transduce and express the fusion antigen Ag85A-E6 in vitro and in vivo . Moreover, a single footpad injection of targeted lentivectors could elicit strong T-helper 1 (Th1) immunity against the above mentioned antigen, as indicated by the specific high-level production of IFN-γ and IL-2 using spleen lymphocytes and lymphoproliferative responses. Despite of these promising results, more attempts are required to elucidate the protective and therapeutic efficacy of this approach in future.